CONCEPTUAL PERSPECTIVES ON PRODUCTION: THE ROLE OF LABOR, CAPITAL, AND TECHNOLOGY IN VALUE CREATION - Yunita Sopiana; Eny Fahrati (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2026)
Production plays a fundamental role in economic activities by utilizing labor, capital, and technology to generate goods and services that create economic value. This study aims to conceptually analyze the role of labor, capital, and technology in modern production processes and their contribution to value creation. The research employs a qualitative approach, using library research to review scholarly articles, books, and international research publications on production theory and economic growth. The findings indicate that technological advancement significantly improves productivity and production efficiency, while labor quality and capital investment remain essential in supporting sustainable production systems. However, rapid technological development also presents challenges to labor markets due to changes in job structures and skill requirements. The study concludes that effective integration of labor, capital, and technology is crucial in achieving sustainable economic value creation in modern production systems.